Transition to the Faculty Role: A Qualitative Study into the Experiences of Nursing Faculty - SEYYED ABOLFAZ VAGHARSEYYEDIN; HAKIMEH SABEGHI (Journal of Advances in Medical Education and Professionalism)
Introduction: The quality of nursing education depends on the availability of faculty members with great professional knowledge and clinical work experience. Thus, novice faculty may face challenges in providing quality education. The aim of this study was to explore the experience of transition to a faculty role among a sample of Iranian nursing faculty.Methods: This qualitative study was conducted in 2022. A total of fifteen faculty members of the nursing and midwifery schools participated in this study. Participants were recruited through purposeful sampling. Data were collected through semistructured interviews and analyzed through Graneheim and Lundman’s conventional content analysis approach.Results: 704 primary codes were generated and grouped into 35 subcategories, nine main categories, and three main themes, namely unpreparedness for the faculty role, abandonment in anon-empathetic workplace, and a road to resilience.Conclusion: Nursing faculty members with limited work experience are unprepared for the transition to faculty roles, receive limited support at work, and rely on personal resources and support networks to facilitate their transition to the faculty role. Further studies are needed to assess the effects of preparation and support programs on the transition to faculty roles among the faculty members with no previous clinical work experience.